Membangun Budaya Perilaku Positif dan Self Awareness Siswa : Kampanye 'Teman Baik Tidak Membully' - Fida Syaina; Puspita Devi; Fadhil Dzaki Agawan; Yuni Saftika; Ahmad Dani; Femas Okta Wijaya (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service activity aims to build a culture of positive behavior among students through the "Good Friends Don't Bully" campaign implemented at Madrasah Ibtidaiyah (MI) Baitul Hikmah, Sri Mulya Village, Ogan Komering Ulu. This campaign aims to increase students' awareness of the negative impacts of bullying and the importance of establishing healthy friendships and supporting a harmonious learning environment. The methods used in this program include educational activities such as counseling, simulations, interactive games, and group discussions designed to increase students' empathy and understanding of the importance of respecting friends. In addition, training for teachers was also conducted to strengthen their role in preventing and handling bullying cases. The results of the activity showed an increase in students' understanding of the concept of bullying and its impacts, as well as the emergence of positive behavioral changes reflected in students' social interactions in the school environment. Teachers also responded positively to this program and are committed to continuing efforts to prevent bullying. With this program, it is hoped that a more positive school culture will be created and support the development of students' character holistically, as well as reduce the number of bullying behaviors in the madrasah environment.